2018
DOI: 10.1039/c7ra13428b
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering through electron transport layer modification for high efficiency organic solar cells

Abstract: Schematic of PTB7-Th:PCBM OSCs in an inverted geometry with ZnO, ZnO/Ba(OH)2 and ZnO:Ba(OH)2 nanocomposites as ETLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…In addition, modification of ZnO with pyridine‐based small molecules also showed smooth surface morphology and higher hydrophobicity than that of ZnO, which is beneficial for better interfacial contact with the active layer. Borse et al 212 used ZnO/Ba (OH) 2 as CIL in inverted OSCs and demonstrated enhanced performance than neat ZnO‐based interlayer. It was observed that the bilayer CIL had a low work function and relatively smooth surface morphology as compared to pristine ZnO.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…In addition, modification of ZnO with pyridine‐based small molecules also showed smooth surface morphology and higher hydrophobicity than that of ZnO, which is beneficial for better interfacial contact with the active layer. Borse et al 212 used ZnO/Ba (OH) 2 as CIL in inverted OSCs and demonstrated enhanced performance than neat ZnO‐based interlayer. It was observed that the bilayer CIL had a low work function and relatively smooth surface morphology as compared to pristine ZnO.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…6. shows the Nyquist plot of the devices with and without Cd-doped buffer layer, which was measured in dark condition, 5% CZO ETL significantly lower than other devices, indicating more efficient electron extraction and reducing interfacial charge recombination at interface [38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the implementation of ZnO/TiO 2 bilayer as ETM for Sb 2 S 3 solar cells has a beneficial influence on the interface properties and indirectly validates the energy band as sketched in Figure 2c, where the conduction band edges are reported to be −4.3 eV (ZnO), −4.2 eV (TiO 2 ), and −3.7 eV Sb 2 S 3 . [ 5,35 ]…”
Section: Resultsmentioning
confidence: 99%